2020
DOI: 10.1016/j.buildenv.2020.106804
|View full text |Cite
|
Sign up to set email alerts
|

Review of multi‐domain approaches to indoor environmental perception and behaviour

Abstract: Building occupants are continuously exposed to multiple indoor environmental stimuli, including thermal, visual, acoustic, and air quality related factors. Moreover, personal and contextual aspects can be regarded as additional domains influencing occupants' perception and behaviour. The scientific literature in this area typically deals with these multiple stimuli in isolation. In contrast to single-domain research, multi-domain research analyses at least two different domains, for example, visual and thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(92 citation statements)
references
References 245 publications
(189 reference statements)
1
71
0
Order By: Relevance
“…In order to address the complexity of human-building interactions, the multifactorial nature of human experience in the built environment should be acknowledged and gradually integrated into soundscape models. Moving beyond single-domain perspectives where each environmental stimulus is studied in isolation, multi-domain approaches are highly encouraged [10,99]. As people experience the thermal, visual, acoustical, and olfactory environments simultaneously, multi-domain research allows for the investigation of interaction effects between multiple environmental factors on building occupants´ perception and cognitive performance [62].…”
Section: Defining Indoor Soundscape Descriptors Under a Multi-domain mentioning
confidence: 99%
“…In order to address the complexity of human-building interactions, the multifactorial nature of human experience in the built environment should be acknowledged and gradually integrated into soundscape models. Moving beyond single-domain perspectives where each environmental stimulus is studied in isolation, multi-domain approaches are highly encouraged [10,99]. As people experience the thermal, visual, acoustical, and olfactory environments simultaneously, multi-domain research allows for the investigation of interaction effects between multiple environmental factors on building occupants´ perception and cognitive performance [62].…”
Section: Defining Indoor Soundscape Descriptors Under a Multi-domain mentioning
confidence: 99%
“…Overall, the ASHRAE Guideline 10 reflects the current state-of-art in research regarding multi-domain IEQ in a clear and honest way. It does not pretend that the effect of interactions between IEQ domains are known, but clarifies already in the foreword that "current knowledge on interactions between and among factors that most affect occupants of indoor environments is limited" as recently confirmed by a comprehensive review [2]. The lack of consensus and available systematic research logically results in the absence of performance indicators or criteria.…”
Section: Evaluation Methods and Consideration Of Interactionsmentioning
confidence: 99%
“…A tacit assumption thereby appears to be that achieving "best performance" in individual domains results in an overall optimum performance at the building level. Recently, efforts are being made to provide the necessary knowledge base for formulation of integrated multi-aspect building design support resources and procedures [2]. In this context, the present contribution explores the current state of multi-domain IEQ evaluation approaches and the necessary conditions for their further development and application.…”
Section: The Need For Integrative Occupant-centric Standardsmentioning
confidence: 99%
“…The current state of knowledge and practice reveals a number of gaps and related research questions regarding building occupants' perceptual and behavioral phenomena [49][50][51]. Broadly speaking, these knowledge gaps may be formulated as follows:…”
Section: Existing Challengesmentioning
confidence: 99%
“…The state-of-the-art review has identified a number of knowledge gaps concerning the multi-domain nature of indoor environmental exposure, the relevance of respective perception and behavior models, and the typology and utility of interfaces for buildings' control devices. Moreover, a number of necessary foundational state-of-the-art reviews have been conducted to address these gaps [49][50][51]. Consequently, research specific priorities are emerging, which are briefly described as follows -and then in more detail in the following sections.…”
Section: Research Prioritiesmentioning
confidence: 99%